2021
DOI: 10.1111/pce.14137
|View full text |Cite
|
Sign up to set email alerts
|

ABA regulation of root growth during soil drying and recovery can involve auxin response

Abstract: Abscisic acid (ABA) plays an important role in plant adaptation to water deficits, but its role in regulating root growth (primary root elongation and lateral root number) during different drought-phases remains unclear. Here, we exposed wild-type (WT) and ABA-deficient (not) tomato plants to three continuous drought-phases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Studies on ABA-deficient mutants have revealed that ABA is important to maintain root growth under drought [86]. Recently, Zhang et al [87] concluded that ABA-mediated root growth of tomatoes under soil drying may involve auxin-dependent processes. ABA deficient mutants vp5 and vp14 develop stunt primary root in maize [88], but primary root elongation is resorted by exogenous IAA in tomato mutant notabilis (not) under drought [87].…”
Section: Alteration In Root System Under Drought 41 Root System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies on ABA-deficient mutants have revealed that ABA is important to maintain root growth under drought [86]. Recently, Zhang et al [87] concluded that ABA-mediated root growth of tomatoes under soil drying may involve auxin-dependent processes. ABA deficient mutants vp5 and vp14 develop stunt primary root in maize [88], but primary root elongation is resorted by exogenous IAA in tomato mutant notabilis (not) under drought [87].…”
Section: Alteration In Root System Under Drought 41 Root System Architecturementioning
confidence: 99%
“…Recently, Zhang et al [87] concluded that ABA-mediated root growth of tomatoes under soil drying may involve auxin-dependent processes. ABA deficient mutants vp5 and vp14 develop stunt primary root in maize [88], but primary root elongation is resorted by exogenous IAA in tomato mutant notabilis (not) under drought [87]. However, ABA affects root architecture either positively or negatively based on the genotypic background and environmental conditions, offering a nuanced way to fine-tune the root system to compete with drought stress.…”
Section: Alteration In Root System Under Drought 41 Root System Architecturementioning
confidence: 99%
“…More research is required to identify the key root phenotype(s) and signals which impact ψ c soil, since root hydraulic phenotypes that trigger earlier stomatal closure would help save water, whereas those that maintain transpiration during soil drying would (potentially) help maintain growth. In this issue Zhang et al (2022) report that signals from the plant hormones abscisic acid (ABA) and auxin play important roles to help maintain tomato root growth during soil drying. The authors applied a multi‐phasic water stress treatment, first involving moderate water stress (3 weeks), then severe drying (2 weeks), followed by re‐watering (3 days), to both wildtype and notabilis ( not ) ABA biosynthesis mutant plants.…”
Section: Water Uptake: More Than Just Deep Root Growthmentioning
confidence: 99%
“…In plants, drought stress induces a wide range of responses, including increasing the oxidative damage in chloroplasts, inhibiting photosynthesis, suppressing metabolic responses, activating glycocatabolism, and changing cellular lipid compositions ( Mittler and Blumwald, 2015 ; Yi et al, 2016 ; Li et al, 2019 ; Hrmova and Hussain, 2021 ; Waititu et al, 2021 ). ABA is the key phytohormone that mediates drought tolerance and rehydration compensation in plants ( Saradadevi et al, 2017 ; Mega et al, 2019 ; Zhang et al, 2021 ). Upon rehydration, the levels of ABA and several other hormones, including IAA, GA, and cytokinin, first decline rapidly and then rise slowly, resulting in a “V”-shaped changing pattern ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%